Pendampingan Pemanfaatan Aplikasi Al-Qur’an for Tahfiz sebagai Media Pembelajaran di Pesantren - Laila, Azzah Nor; Rahmawati, Ana; Azizah, Noor; Chasanah, Muallimatul (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The tahfiz program is featured in several Islamic Education Institutions, but several institutions experience problems with achieving less targets and limited media innovation. So the community service team partnered with the Jepara Regency Islamic Boarding School Group Forum (FKPP), aimed to provide senior students with an understanding of the development of digital media, and the use of the Al-Qur'an application for tahfiz in Islamic boarding schools. The method for this service used Participatory Action Research (PAR), and at the training stage used lectures, discussions, tutorials, and practical assistance. The stages of the activity include preparation, outreach, training, mentoring, and evaluation. The results show that community service activities have been carried out in the Jepara Regency FKPP hall in Mangunan Jepara. The activity participants totaled 30 participants, from FKPP management and representatives of senior students from 10 tahfiz Islamic boarding schools. The result is that 80% of participants understand the development of digital media, 75% of students can use the Al-Qur'an for tahfiz application as a medium for memorizing and muraja'ah. In the evaluation aspect, in general the participants' responses were very good, the material according to the needs of the students was responded to by 57% strongly agreeing, 43% agreeing. Submission of clear and comprehensive sources was responded to by 57% and 43%. In the aspect of implementation, responses regarding the course of activities as expected reached 57% and 43% agreed. Adequate activity time was responded to by 52% strongly agree, and 48% agree. Services during satisfying activities were responded to by 57% strongly agreeing, and 43% agreeing. At the application level, partners respond that the Al-Qur'an for tahfiz application is very helpful, students can find the same verses that are often inverted when memorizing to anticipate and remember.